Chemistry - Dwyer, Jon; Poole, Emma (London : Letts Educational, 2011)
This complete revision and study guide has everything you need to achieve the grade you want: detailed course notes to support independent study, sample GCSE questions and answers so that you know what the examiner is looking for, and lots of GCSE-style questions for invaluable exam practice.
Includes index.
Keywords: Chemistry -- Examinations -- Study guides; Popular Science and Mathematics